Analisis Representasi Gender Dalam Laporan Tahunan Bank Pembangunan Daerah Di Indonesia - Putri Oktalia; Herlina Helmy (Universitas Negeri Padang, 2020)
This study aims to provide analysis and understanding of gender representation in the annual report of the Regional Development Bank (BPD) in Indonesia. The objects of this research are PT Bank Aceh and PT Bank DKI Jakarta. The study uses a qualitative descriptive approach with secondary data types obtained from the Annual Report of PT Bank Aceh and Bank DKI. Data collection is done by documentation techniques by collecting photographs of humans in the company's annual report. The analytical method used is content analysis. The steps of this research are: 1) identifying photos of people in the annual report, 2) grouping photos by employees or non-employees, only men, only women, or men and women together, 3) overview of the quantity of photos by group, 4) interpret the results of research found in the annual report. The results showed that gender portrayals in the BPD Aceh and DKI Jakarta annual reports did not support equality between men and women. Employee photos in the annual report are dominated by male gender compared to female. Through analysis of gender photographs described in the annual report it was found that male gender dominates in terms of roles, places, clothing and body language. But in the analysis of the relative position, men and women are shown standing or sitting equally.